FrAMC-i: um framework de apoio à produção de conteúdo multimídia complementar interativo - Rodrigues, Kamila Rios da Hora (2014)
The television is the medium of information and entertainment most utilized by Brazilians. Despite its great reach, this vehicle, which should be an instrument to promote social inclusion, often causes the opposite effect. The manner some television programs are produced, in particular movies and series, combined with the lack of prior knowledge about certain subjects and contexts, trigger some viewers not to appreciate or enjoy enough of the programming, which may lead to a possible dissatisfaction in the audience. Cultural and educational matters may also accentuate the viewer's discontentment during a television session. New technologies such as the Interactive Digital TV (IDTV) allow the enrichment of television media with additional contents that may provide greater fruition of the narratives. This PhD project benefits from the flexibility and interactivity offered by the IDTV to propose a solution of accessibility based on the offer of additional specific contents, here denominated interactive Additional Multimedia Content (AMC-i). The AMC-i are extra information associated with the television media that may be offered to the main program considering different aspects, such as whether the offer: is synchronous or asynchronous, on demand or compulsory, with or without pausing the original program, by combining one or more media formats, among others. Through case studies, groups of spectators with distinct profiles, in different scenarios and interacting with varying kinds of media, were observed and had their interaction difficulties and experiences evaluated. This thesis proposes and presents the FrAMC-i, a framework consisting of a set of guidelines that support the production of AMC-i and emerged from the experience acquired during the observation of spectators in the studies. In addition to the guidelines, the FrAMC-i also provides tools for the enrichment of the media with AMC-i and a mobile application that enables the interaction with such contents by usage of a second screen. The framework was submitted to assessment by sixteen graduate students in Computer Science in the role of designers. These evaluators used the FrAMC-i artifacts to enrich media, given a provided fictional scenario. The results suggest a positive evaluation considering the utility, adherence to the proposed design solutions and usability of the artifacts supplied by the framework for the different stages of the production of the AMC-i.